Pengembangan Media Smart Box Berbasis Qr Code pada Mata Pelajaran IPS Kelas V - Arum Kumala; Yuni Krisnawati; Andri Valen (JOEAI (Journal of Education and Instruction), 2026)
This study aims to develop a valid, practical, and effective QR Code-based Smart Box media for fifth-grade social studies at SDN 38 Lubuklinggau. This research is a Research and Development study using the ADDIE development model. The results showed that the language validator scored 0.89, the media validator scored 0.90, and the material validator scored 0.96, meeting the validity criteria. Analysis of the teacher and student practicality assessment sheets showed that the QR Code-based Smart Box media met the criteria for being very practical, with an average score of 91.91%. Furthermore, the effectiveness assessment obtained an average N-Gain score of 0.79, categorized as high. Based on the results, it can be concluded that the QR Code-based Smart Box media is valid, practical, and effective, making it suitable for use in Chapter 7, "My Region, My Pride," Topic A, "What is the Culture of My Region?", at fifth-grade SDN 38 Lubuklinggau.   Keywords: Social Studies; Smart Box Media; Development; QR Code; Elementary School